Effects of Selenium on Growth and Selenium Content Distribution of Virus-Free Sweet Potato Seedlings in Water Culture - Chen, Huoyun; Cheng, Qun; Chen, Qiaoling; Ye, Xingzhi; Qu, Yong; Song, Weiwu; Fahad, Shah; Gao, Jianhua; Saud, Shah; Xu, Yi; Shen, Yanfen (Frontiers in Plant Science, 2022)
Understanding the selenium tolerance of different sweet potato [Dioscorea esculenta (Lour.) Burkill] is essential for simultaneously for breeding of new selenium-tolerant varieties and improving the selenium content in sweet potato. Therefore, a greenhouse experiment was conducted from February to April 2022 to evaluate the effect of sweet potato cultivars and selenium (Na2SeO3) concentrations (0–40 mg/L) on plant growth, physiological activities and plant selenium content distribution. The results showed that when the selenium concentration was more than 3 mg/L, the plant growth was significantly affected and the plant height and root length were significantly different compared to the control. While the selenium concentration was 20 and 40 mg/L had the greatest effect on plant growth when the number of internodes and leaves of the plant decreased, the root system stopped growing and the number of internodes of the plant, the number of leaves and the dry-to-fresh weight ratio of the plant a very significant level compared to reached control. The relative amount of chlorophyll in leaves under treatment with a selenium concentration of 1 mg/L was increased, and the relative amount of chlorophyll in 3 mg/L leaves gradually increased with the increase in the selenium concentration. The values of the maximum photochemical efficiency PSII (fv/fm) and the potential activity of PSII (fv/fo) compared to the control under treatment with 40 mg/L selenium concentration and photosynthesis of plants was inhibited. The selenium content in root, stem and leaf increased with the increase in selenium concentration, and the distribution of selenium content in the plant was leaf <stem <root, and the selenium content in root was significantly higher than that in stem and leaf. In summary, the appropriate concentration of selenium tolerance has been determined to be 3 mg/L. The aquatic culture identification method of selenium tolerance of sweet potatoes and growth indices of various selenium tolerant varieties (lines) established in this study will provide a technical basis for selenium tolerant cultivation and mechanism research.